2018
DOI: 10.1186/s12885-018-4890-8
|View full text |Cite
|
Sign up to set email alerts
|

Human papillomavirus infection in patients with laryngeal carcinoma

Abstract: BackgroundThe aim of this study was to determine the HPV positivity rate in patients with laryngeal cancer, and to determine the effect of HPV positivity on survival. An additional aim was to determine if patients with HPV positive laryngeal cancer are more sensitive to chemotherapy and if such sensitivity differs according to chemotherapy protocol.MethodsThe study included laryngeal specimens obtained from 82 laryngeal cancer patients and 11 laryngeal specimens with normal laryngeal mucosa that were obtained … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 24 publications
1
9
0
1
Order By: Relevance
“…Also, another study by Kreimer et al has shown that the rate of infection with HPV in laryngeal cancer tissue was 24%, which is in agreement with our results, but also showing that a 19% HPV infection rate was seen in normal laryngeal mucosa as well [27]. In accordance with other studies, our results have shown 18.2% HPV-driven laryngeal cancer [26,29], compared to studies that showed a lower association [30,31].…”
Section: Discussionsupporting
confidence: 93%
“…Also, another study by Kreimer et al has shown that the rate of infection with HPV in laryngeal cancer tissue was 24%, which is in agreement with our results, but also showing that a 19% HPV infection rate was seen in normal laryngeal mucosa as well [27]. In accordance with other studies, our results have shown 18.2% HPV-driven laryngeal cancer [26,29], compared to studies that showed a lower association [30,31].…”
Section: Discussionsupporting
confidence: 93%
“…Согласно другим литературным данным, ВПЧ является причиной от 0 до 44% случаев рака полости рта, от 0 до 86 -ротоглотки, от 0 до 36%гортани. Столь большой разброс может быть объяснен демографическими особенностями популяции и разными методами как обнаружения, так и экстраполяции [25].…”
Section: вирус эпштейна-баррunclassified
“…Hypopharynx, which show low, or no HPV positivity, is sometimes included with laryngeal region for HPV prevalence studies. Data presented in the figure is derived from different systematic reviews and meta-analyses ( Miller and Johnstone, 2001 ; Syrjanen, 2003 ; Kreimer et al, 2005 ; Sarkola et al, 2008 ; Rautava and Syrjanen, 2011 ; Syrjanen et al, 2017 ; Onerci Celebi et al, 2018 ). [Image originally produced by Macmillan Cancer Support and reused with permission].…”
Section: Hpv In Handn Region and Association With The Cancer Causationmentioning
confidence: 99%